Capping β‐hairpin with N‐terminal d‐amino acid stabilizes peptide scaffold. Issue 3 (May 2016) - Makwana, Kamlesh M.; Mahalakshmi, Radhakrishnan
ABSTRACT: Various strategies exist to stabilize de novo designed synthetic peptide β‐hairpins or β‐sheets structures, especially at the non‐hydrogen bonding position. However, strategies to stabilize strand termini, which are affected by fraying, are highly limited. Here, by substituting N‐terminal aliphatic amino acid with its mirror image counterpart, we achieve a significant increase in scaffold stabilization, resulting from the formation of a terminal aliphatic–aromatic hydrophobic CH…pi cluster. Our extensive solution NMR studies support the incorporation of an N‐terminald‐ aliphatic amino acid in the design of short β‐hairpins, while successfully retaining the overall structural scaffold. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 260–266, 2016.